Hypoglycemic Effect of the N-Butanol Fraction of Torreya grandis Leaves on Type 2 Diabetes Mellitus in Rats through the Amelioration of Oxidative Stress and Enhancement of β-Cell Function. (28th December 2022) - Li, Xue-Qin; Jia, Shan-Shan; Yuan, Ke; Jin, Song-Heng
Abstract : Content . The water and ethanol extracts of Torreya grandis ( T. grandis ) have antioxidant, antibacterial, and hypolipidemic effects . Objective . The hypoglycemic effect and mechanism of the n-butanol fraction of the 75% ethanol extract of T. grandis leaves (BFTL) on rats with streptozotocin- and high-fat diet-induced type 2 diabetes mellitus (T2DM) were investigated. Materials and Methods . Sprague–Dawley rats were randomly divided into six groups: control, T2DM, metformin, high-dose BFTL (800 mg/kg), middle-dose BFTL (400 mg/kg), and low-dose BFTL (200 mg/kg). After 4 weeks of BFTL treatment, the correlations of serum indicators with protein expression in tissue were determined, and pathological changes in the liver, kidneys, and pancreas were analyzed. Results . Compared with the results in the T2DM group, serum fasting blood glucose, triglyceride, total cholesterol, malondialdehyde, alanine aminotransferase, and aspartate aminotransferase levels were significantly decreased ( p < 0.05 ), whereas superoxide dismutase and glutathione peroxidase levels were significantly increased ( p < 0.05 ) in the high-, middle-, and low-dose BFTL groups. The treatment also improved oral glucose tolerance. In addition, the pathological changes of the liver, kidney, and pancreas were improved by BFTL treatment. Cytochrome and caspase-3 expression in pancreatic was significantly decreased ( p < 0.05 ) by BFTL treatment, whereas the Bcl-2/Bax ratio was significantly increased ( p < 0.05 ). Discussion and Conclusion . BFTL exerted significant hypoglycemic effect on T2DM model rats, and its mechanism involved the suppression of blood glucose levels and oxidative stress by improving the metabolism of blood lipids and antioxidant capacity, boosting β -cell function, and inhibiting β -cell apoptosis.